15% efficient carbon based planar-heterojunction perovskite solar cells using a TiO2/SnO2 bilayer as the electron transport layer. Issue 17 (28th March 2018) - Liu, Zhiyong; Sun, Bo; Liu, Xingyue; Han, Jinghui; Ye, Haibo; Tu, Yuxue; Chen, Chen; Shi, Tielin; Tang, Zirong; Liao, Guanglan
Abstract : Low-temperature printable carbon based planar-heterojunction perovskite solar cells with efficiencies exceeding 15% were demonstrated by using a TiO2 /SnO2 bilayer as ETL together with CuPc as HTL. Abstract : Perovskite solar cells (PSCs) are one of the most promising lab-scale technologies to deliver inexpensive solar electricity. Low-temperature printable carbon counter electrode based planar-heterojunction PSCs are particularly suitable for future large-scale manufacturing, but suffer from an inferior efficiency. Here, we demonstrate a TiO2 /SnO2 bilayer as the electron transport layer (ETL) for carbon counter electrode based planar-heterojunction PSCs together with micromolecule Cu-phthalocyanine (CuPc) as the hole transport layer (HTL), yielding a high power conversion efficiency of 15.39% and an excellent stability over 1200 h. The improved performances are attributed to a better energy level transition, a suppressed electron–hole recombination, and a wider depletion region of the TiO2 /SnO2 bilayer. Our work represents a great advancement in the fabrication and popularization of carbon counter electrode based PSCs. More importantly, the whole devices are processed at a temperature below 200 °C, providing potential application of PSCs in monolithic tandem devices and paving the way for the development of carbon based flexible PSCs.